2017
DOI: 10.1038/s41598-017-12499-w
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophilic Functionalization of Microfiltration Ceramic Membranes Enables Separation of Hydrocarbons from Frac and Produced Water

Abstract: The environmental impact of shale oil and gas production by hydraulic fracturing (fracking) is of increasing concern. The biggest potential source of environmental contamination is flowback and produced water, which is highly contaminated with hydrocarbons, bacteria and particulates, meaning that traditional membranes are readily fouled. We show the chemical functionalisation of alumina ceramic microfiltration membranes (0.22 μm pore size) with cysteic acid creates a superhydrophilic surface, allowing for sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…As previously alluded to, our understanding of the modified ceramic separation capabilities changed during the preliminary investigations into their use for this study. Previous and ongoing work using frack-produced water has demonstrated that the membranes are capable of cleaning water at the molecular level [ 32 ]. These waters are heavily contaminated far beyond solubility limits, resulting in biphasic mixtures and oil–water emulsions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously alluded to, our understanding of the modified ceramic separation capabilities changed during the preliminary investigations into their use for this study. Previous and ongoing work using frack-produced water has demonstrated that the membranes are capable of cleaning water at the molecular level [ 32 ]. These waters are heavily contaminated far beyond solubility limits, resulting in biphasic mixtures and oil–water emulsions.…”
Section: Resultsmentioning
confidence: 99%
“…The project initiated between Swansea University and Company A was to develop a system of removing organic matter contamination from groundwaters on various sites with an initial test site located in the UK. The methodology used in this study was to be based upon the development of a novel super-hydrophilic ceramic membrane system as previously reported [ 31 , 32 ]. Preliminary investigations from this project increased operational understanding of the separation mechanisms of the modified ceramic membrane and have shown that the membrane is very good for separations where the contamination levels are very high.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophilic organic polymers with reactive groups are also used to prepare superhydrophilic and underwater superoleophobic ceramic membranes. Maguire-Boyle et al [132] created a superhydrophilic surface on alumina ceramic MF membranes with cysteic acid (HO 2 CCH(NH 2 )CH 2 SO 3 H) by chemical functionalization. The TMP was much lower for the modified membrane to obtain the same flux than that of the unmodified one.…”
Section: Superhydrophilic Ceramic Membranementioning
confidence: 99%
“…Table 11 Advantages and disadvantages of ceramic membranes as compared to polymeric membranes [410]. Oily water is typically treated using MF [411], UF [412], and NF [413] ceramic membranes. MF membranes were also used to separate oil, grease and suspended solids from produced water [269].…”
Section: Ceramic Membranes For Oily Water Separationmentioning
confidence: 99%